Pervasive computing for quality of life enhancement : 5th International Conference on Smart Homes and Health Telematics, ICOST 2007 Nara, Japan, June 21-23, 2007 : proceedings - ICOST; 岡留, 剛; 山崎, 達也; Makhtari, Mounir (Lecture Notes in Computer Science, 2007)
This book constitutes the refereed proceedings of the 5th International Conference On Smart Homes and Health Telematics, ICOST 2007, held in Nara, Japan in June 2007. It presents the latest approaches and technical solutions in the area of smart homes, health telematics, and emerging enabling technologies.